2022
DOI: 10.3390/children9040513
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Emergencies and Hospital Admissions in the First Six Months of the COVID-19 Pandemic in a Tertiary Children’s Hospital in Romania

Abstract: The COVID-19 pandemic has had a significant impact on the pediatric population, particularly on their access to health services. We conducted a retrospective study to assess the influence that the pandemic, and its related containment and mitigation public health measures, had on pediatric emergencies and hospitalizations in a major tertiary pediatric hospital in Bucharest, Romania, during the first six months of the pandemic, March–August 2020, compared to the same period in 2019. In these first 6 months of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Increased concern about the new condition, might prompt more hospital admissions in the early phase of the COVID-19 pandemic. Literature, however, suggests that an increased fear of possible infection with SARS-CoV-2, resulted in a reduction of medical consultation and hospital admission for respiratory infections [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Increased concern about the new condition, might prompt more hospital admissions in the early phase of the COVID-19 pandemic. Literature, however, suggests that an increased fear of possible infection with SARS-CoV-2, resulted in a reduction of medical consultation and hospital admission for respiratory infections [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cases included in the analysis were from the pre-pandemic period, which can be explained by the fact that viral circulation and hospitalizations in the pediatric population were significantly influenced by the COVID-19 pandemic and the temporary prevention measures implemented [ 27 , 28 , 29 ]. We identified that digestive symptoms (95.2%) were predominant in most children, especially diarrhea (90.5%) and vomiting (50.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The volume of pediatric emergency department visits and admissions also declined throughout the COVID-19 pandemic ( DeLaroche et al., 2021 ; Moynihan et al., 2021 ; Miron et al., 2022b ). A comprehensive systematic review further documented a 37% reduction in overall healthcare services, encompassing a 42% and 28% decrease in visits and admissions, respectively ( Moynihan et al., 2021 ).…”
Section: "Declines" In Infectious Diseases In Children During the Ear...mentioning
confidence: 99%